Transcriptomic Analyses of Inner Ear Sensory Epithelia in Zebrafish. Issue 3 (28th December 2019) - Yao, Qi; Wang, Lingyu; Mittal, Rahul; Yan, Denise; Richmond, Michael T.; Denyer, Steven; Requena, Teresa; Liu, Kaili; Varshney, Gaurav K.; Lu, Zhongmin; Liu, Xue Zhong
Abstract : Analysis of gene expression has the potential to assist in the understanding of multiple cellular processes including proliferation, cell‐fate specification, senesence, and activity in both healthy and disease states. Zebrafish model has been increasingly used to understand the process of hearing and the development of the vertebrate auditory system. Within the zebrafish inner ear, there are three otolith organs, each containing a sensory macula of hair cells. The saccular macula is primarily involved in hearing, the utricular macula is primarily involved in balance and the function of the lagenar macula is not completely understood. The goal of this study is to understand the transcriptional differences in the sensory macula associated with different otolith organs with the intention of understanding the genetic mechanisms responsible for the distinct role each organ plays in sensory perception. The sensory maculae of the saccule, utricle, and lagena were dissected out of adult Et(krt4:GFP) sqet4 zebrafish expressing green fluorescent protein in hair cells for transcriptional analysis. The total RNAs of the maculae were isolated and analyzed by RNA GeneChip microarray. Several of the differentially expressed genes are known to be involved in deafness, otolith development and balance. Gene expression among these otolith organs was very well conserved with less than 10% of genes showing differential expression. Data from this study will help to elucidate which genes are involved in hearing and balance. Furthermore, the findings of this study will assist in the development of the zebrafish model for human hearing and balance disorders. Anat Rec, 303:527–543, 2020. © 2019 American Association for Anatomy